CPM Analysis on Boarding House Construction Projects in Samarinda City - Suramli, Suramli; Fredi, Natalia; Wijaksana, I Made Arya Abdi; Putri, Feby Resti; Rongko, Santa Melisa Sindi (Journal of Business Management and Economic Development, 2024)
Population growth increases the need for practical and affordable housing, so boarding houses become the main choice. Boarding house construction projects need to be managed through good project management. This research discusses the use of the Critical Path Method (CPM) in the boarding house project on Jl. Mangkupalas Gg. Padai in Samarinda City. The CPM method is used to determine project duration and optimize costs, with information on work, costs and time for each stage. The results show the critical activity path A – B – C – E – F – G – H – I – K, reducing the project duration from 210 days to 173 days, 37 days faster. Using the CPM method saves IDR 19,050,000 from the initial project cost of IDR 298,939,000 to IDR 279,889,000. This research supports the CPM method for cost and time efficiency in development projects and the results of this research are in accordance with previous studies which also discusses the CPM method of project management.